2021
DOI: 10.3390/su132111575
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Cities Seen from Loyalty and Their Tourist Motivations: A Study in Lima, Peru

Abstract: The objective of this empirical study is to determine: (a) the underlying variables of the travel motivations related to a coastal city; and (b) the motivational dimensions that predict return, recommendation, and saying positive things about a coastal city as loyalty variables. This project utilized an in situ investigation carried out in Lima, a coastal city located on the Pacific Ocean near Peru with important natural and cultural attractions. The researchers used 381 questionnaires that were analyzed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several scholars have reported tourist satisfaction as a mediator in revisiting various contexts. For example, the TS established the indirect effect of sustainability practices [127], destination image [128][129][130], perceived value [120,131,132] and novelty seeking [133,134] on intention to revisit through TS. As a result of the previously determined direct association between EFPV and BIVE, the finding indicates that BIVE indirectly (via TS) has a positive and significantly relationship to EFPV.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have reported tourist satisfaction as a mediator in revisiting various contexts. For example, the TS established the indirect effect of sustainability practices [127], destination image [128][129][130], perceived value [120,131,132] and novelty seeking [133,134] on intention to revisit through TS. As a result of the previously determined direct association between EFPV and BIVE, the finding indicates that BIVE indirectly (via TS) has a positive and significantly relationship to EFPV.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, special-interest tourism within cities has gained increasing popularity. Some scholars examined the motivations of specific segments of the city tourists, such as winter sports tourists (Bichler & Pikkemaat, 2021), cultural tourists (Kay Smith, Pinke-Sziva, Berezvai, & Buczkowska-Gołąbek, 2022), culinary tourists (Nicoletti, Medina-Viruel, Di-Clemente, & Fruet-Cardozo, 2019), creative tourists (Remoaldo et al , 2020), heritage tourism (Dai, Hein, & Zhang, 2019; Ramires, Brandao, & Sousa, 2018; Vareiro, Sousa, & Silva, 2021) and coastal city tourism (Carvache-Franco et al , 2021). Another focus for urban tourism motivational studies might be the tourist segments identified on the basis of culture or country of origin, the importance of which is discussed in the next section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3389/fevo.2023.1129556 Frontiers in Ecology and Evolution 03 frontiersin.org relatively severe human-wildlife conflicts within and around PAs, leading to loss of livestock and crops. Additionally, the TGPNP has a strong tourist attraction to the public, thus bringing about tourists and employment opportunities to surrounding communities (Carvache-Franco et al, 2021). Thirdly, the Administration of Tangjiahe Area (ATA) has carried out community-based conservation practices with local communities since 1978, such as joint fire prevention and infrastructure building supports, organizing co-management committees, and China Bee Breeding Cooperative.…”
Section: Study Areamentioning
confidence: 99%
“…• Accessibility to PA boundary: the designation of PA boundary can impose significant impact on local communities by exerting restrictions on land-use and livelihood sources. Since plenty of studies have explored how the proximity to PA boundary can affect locals' conservation attitudes and well-being (Naidoo et al, 2019;Carvache-Franco et al, 2021), it is worth paying attention (Kenneth, 2020). • Accessibility to main roads: as local residents spatially residing across the mountainous area mainly rely on the road traffic to travel to hospitals, schools, and other public facilities, the road accessibility may play an important part in shaping the fairness perceptions of residents (Wang et al, 2021).…”
Section: Construction Of the Variable Set For Spatial Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation